2020
DOI: 10.1029/2020ja027967
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Dependence of the Formation of Electron Butterfly Pitch Angle Distribution Driven by Magnetosonic Waves

Abstract: Using the full relativistic test particle (TP) simulation code, we investigate the parametric dependence of electron scattering and phase space density evolution driven by magnetosonic (MS) waves at L = 4.5 both inside and outside the plasmapause. The scattering effects caused by Landau resonance, bounce resonance, and the transit-time effect are all involved in the study. The net scattering effects are evaluated in the form of diffusion coefficients with different combinations of MS wave parameters, such as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
(125 reference statements)
0
11
0
Order By: Relevance
“…We use the TPS (S. Fu & Ge, 2021; S. Fu, Ni, Tao, et al., 2019; S. Fu et al., 2020; Zhou et al., 2020) to investigate the combined effect with multi‐resonance mechanisms by ELF chorus waves on electrons. The detailed description about the TPS method can be found in the Supporting Information .…”
Section: Analysis Resultsmentioning
confidence: 99%
“…We use the TPS (S. Fu & Ge, 2021; S. Fu, Ni, Tao, et al., 2019; S. Fu et al., 2020; Zhou et al., 2020) to investigate the combined effect with multi‐resonance mechanisms by ELF chorus waves on electrons. The detailed description about the TPS method can be found in the Supporting Information .…”
Section: Analysis Resultsmentioning
confidence: 99%
“…The plasmasphere, which is full of cold and dense plasma (electrons ∼1 eV with density ∼10 2 –10 4 cm −3 ), plays an important role in modulating the fluxes of energetic particles in the Earth's ring current and radiation belts (e.g., Cao et al., 2017; Darrouzet et al., 2009; Fu et al., 2020; Gu et al., 2011, 2012, 2020; Hua et al., 2019; Kozyra et al., 1995; Lemaire & Gringauz, 1998; Ni et al., 2013; Orr & Webb, 1975; Sandel et al., 2003; Takahashi & Anderson, 1992; Webb & Orr, 1975; Yi et al., 2021; Zhou et al., 2020). The plasmasphere strongly influences the plasma properties of the inner magnetosphere by wave‐particle interactions (e.g., Fu et al., 2016; Gary et al., 1994; Hua et al., 2020a; Ni et al., 2017, 2014; Thorne & Horne, 1992; Wilson et al., 1992; Xiang et al., 2018; Young et al., 1981), and contributes to assessing the low‐latitude boundary layer and plasma sheet (e.g., Cao et al., 2016; Elphic et al., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…MS waves are capable of accelerating radiation belt electrons via Landau resonance on a time scale of ∼1 day (Horne et al., 2007; Lei et al., 2017; Li et al., 2014; Li, Bortnik et al.,2016; Li, Ni et al., 2016; Xiao et al., 2015), leading to electron butterfly PADs (Hua et al., 2018; X. Ma et al., 2020; Ni et al., 2020; Yu et al., 2019). Recent studies suggest that MS waves can scatter radiation belt electrons by both Landau and bounce resonances (S. Fu et al., 2019; R. Zhou et al., 2020) and scatter ring current protons by cyclotron resonance (Fu et al., 2016; Fu & Ge, 2021). Hua et al.…”
Section: Introductionmentioning
confidence: 99%
“…MS waves are usually observed in the Earth's magnetosphere both inside and outside the plasmasphere (Li, Bortnik et al., 2017; B. Liu, Li et al., 2018; Ma et al., 2013, 2016, 2019; Meredith et al., 2008) and are generally confined within ±3° of the geomagnetic equator (Ma et al., 2013; Nemec et al., 2005, 2006; Zou et al., 2019; R. Zhou et al., 2020). Both observational and theoretical results have found that MS waves can be excited by a natural instability due to proton ring distributions which are associated with proton injections during the substorms (Boardsen et al., 1992; Chen et al., 2010; Gao et al., 2018; Horne et al., 2000; K. Liu et al., 2011; R. Zhou et al., 2020). It is also reported that MS waves can be generated in the off‐equatorial high‐density plasmasphere (Wu et al., 2021) and the substorm proton injections can quench MS waves under both high‐ and low‐density conditions (Dai et al., 2019).…”
Section: Introductionmentioning
confidence: 99%